Extended Shortwave Infrared T2SL Detector Based on AlAsSb/GaSb Barrier Optimization - Jing Yu; Yuegang Fu; Lidan Lu; Weiqiang Chen; Jianzhen Ou; Lianqing Zhu (Micromachines)
Extended shortwave infrared (eSWIR) detectors operating at high temperatures are widely utilized in planetary science. A high-performance eSWIR based on pBin InAs/GaSb/AlSb type-II superlattice (T2SL) grown on a GaSb substrate is demonstrated. It achieves the optimization of the device’s optoelectronic performance by adjusting the p-type doping concentration in the AlAs0.1Sb0.9/GaSb barrier. Experimental and TCAD simulation results demonstrate that both the device’s dark current and responsivity grow as the doping concentration rises. Here, the bulk dark current density and bulk differential resistance area are extracted to calculate the bulk detectivity for evaluating the photoelectric performance of the device. When the barrier concentration is 5 × 1016 cm−3, the bulk detectivity is 2.1 × 1011 cm·Hz1/2/W, which is 256% higher than the concentration of 1.5 × 1018 cm−3. Moreover, at 300 K (−10 mV), the 100% cutoff wavelength of the device is 1.9 μm, the dark current density is 9.48 × 10−6 A/cm2, and the peak specific detectivity is 7.59 × 1010 cm·Hz1/2/W (at 1.6 μm). An eSWIR focal plane array (FPA) detector with a 320 × 256 array scale was fabricated for this purpose. It demonstrates a remarkably low blind pixel rate of 0.02% and exhibits an excellent imaging quality at room temperature, indicating its vast potential for applications in infrared imaging.